Proximate composition and in vitro protein digestibility of extruded aquafeeds containing Acheta domesticus and Hermetia illucens fractions - Irungu, F.G.; Mutungi, C.M.; Faraj, A.K.; Affognon, Hippolyte D.; Ekesi, S.; Nakimbugwe, D.; Fiaboe, K.K.M. (Brill, 2018)
Major protein sources for feed manufacture have become costly, and this has led to increased cost of products such as aquafeeds. This has dampening effect on fish production especially in developing countries, and has necessitated a search for alternative protein sources in processed feeds. The effects of extrusion on aquafeed blends containing fractions of adult cricket (Acheta domesticus) meal (ACM) or black soldier fly (Hermetia illucens) pre-pupae meal (BSFM) on proximate composition and in vitro protein digestibility were investigated. Extrusion resulted in higher contents of protein and nitrogen free extract, and lower contents of ether extract and crude fibre as compared to the non-extruded feed. These observations were mainly associated with denaturation of proteins leading to increase in solubility, solubilisation of fibre due to the shearing forces at high temperature resulting in higher nitrogen free extract, and formation of starch-lipid complexes leading to lower ether extract. Our findings indicate that ACM or BSFM can be used to substitute fresh water shrimp meal up to 75 g/100 g level and still achieve highly nutritious processed fish feed.